An investigation into linguistic features of speech act verbs in English and Vietnamese newspaper news - Bạch, Thị Liễu.; Phan Văn Hòa, Assoc.Prof.Dr. (ĐHĐN., 2014)
Introduction; Literature review and theoretical background; Methodology and procedure; ...
Keywords: The English language; linguistic features -- newspaper news